Tree regeneration in sacred groves of Kathmandu valley, Nepal - Shrestha, L.J.; Devkota, M.P.; Sharma, B.K. (Ecoprint: An International Journal of Ecology, 2016)
Population structure and regeneration status of tree species were studied in two sacred groves of Kathmandu valley, Pashupati (PSG) and Bajrabarahi (BSG) by sampling in concentric circular plots of 20 m radius. The dominant tree species of PSG are Schima wallichii, Pyrus pashia, Myrsine capitellata, Persea odoratissima and Quercus glauca, where as those in BSG are Neolitsea cuipala, Castanopsis indica,, Choerospondias axillaris, Schima wallichii and, Myrsine capitellata. On the basis of biomass removal, tree cutting, livestock and wildlife grazing and other anthropogenic activities, disturbance levels were classified as undisturbed, least disturbed, moderately disturbed and highly disturbed. The highest number of seedlings, saplings and adults were found in the least disturbed areas of the studied groves showing good to fair regeneration of tree species. In this study Pyrus pashia, Myrsine capitellata, Castanopsis indica, Neolitsea cuipala are found in good and fair state of regeneration. Management authority should address the prevalent factors affecting natural regeneration of the tree species. ECOPRINT 22: 29-38, 2015